2009
DOI: 10.1007/s12576-009-0047-5
|View full text |Cite
|
Sign up to set email alerts
|

Passive mechanical properties of cardiac tissues in heart hypertrophy during pregnancy

Abstract: We evaluated changes in passive mechanical properties in cardiac tissues during rat pregnancy. Left and right ventricular free walls were dissected from hearts of nonpregnant, late-pregnant, and postpartum rats. Mechanical experiments in ventricular strips were done by stretch-release cycles using a step motor. The results show that during pregnancy, there is cardiac hypertrophy associated with (1) an increase in myocyte size, particularly of augmented myocyte length, (2) a decrease in passive tension develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…This can be interpreted as the hormonal response to pregnancy stimulates cardiac stem cells and the generation of new cardiomyocytes, a phenomenon, which has not been described earlier. Previous studies have only implied that during pregnancy the heart adapts to an increased workload by left ventricle hypertrophy [43], [44]. According to our data, there also seems to be hyperplasia involved, through the up-regulation of cardiac progenitors.…”
Section: Discussionsupporting
confidence: 54%
“…This can be interpreted as the hormonal response to pregnancy stimulates cardiac stem cells and the generation of new cardiomyocytes, a phenomenon, which has not been described earlier. Previous studies have only implied that during pregnancy the heart adapts to an increased workload by left ventricle hypertrophy [43], [44]. According to our data, there also seems to be hyperplasia involved, through the up-regulation of cardiac progenitors.…”
Section: Discussionsupporting
confidence: 54%
“…The changes in collagen isoforms expression observed in this work could explain the decrease in cardiac stiffness in late pregnancy reported in previous studies [6], suggesting an adaptive mechanism to compensate the demand of blood volume overload in heart during pregnancy.…”
Section: Resultssupporting
confidence: 70%
“…In human and animals (rats and mice), it has been reported that a prolonged volume overload during pregnancy triggers eccentric cardiac hypertrophy which is reversible in postpartum. This hypertrophy is the result of individual growth of cardiac myocytes, predominantly in the longitudinal axis [5, 6]. The molecular signaling pathways in pathological cardiac hypertrophy and cardiac remodeling have been widely studied; however, the physiological cardiac remodeling induced by pregnancy and the reversion in postpartum are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Although in the whole heart cells are electrically connected and thus the myocardium should behave as a functional syncytium, a remarkable similarity of the electrical interaction with external field has been observed in isolated myocytes and whole hearts of neonatal rats (Gomes et al, 2001(Gomes et al, , 2002. Increase in cell length is known to occur in some physiological (pregnancy; Virgen-Ortiz et al, 2009) and pathophysiological conditions, such as mitral insufficiency (Dillon et al, 2012), spontaneous arterial hypertension (R.A. Bassani, unpublished results), dilated cardiomyopathy (Kaistura et al, 1995), and familial hypertrophic cardiomyopathy (Brouwer et al, 2011). Cardiac hypertrophy has been considered an independent factor associated with increased risk of arrhythmia and sudden death (Bender et al, 2012;Reinier et al, 2011), particularly in the case of hypertrophic cardiomyopathy (Brouwer et al, 2011).…”
Section: Cell Lengthmentioning
confidence: 99%